THE IMPLEMENTATION OF EDUCATIONAL STAFF MANAGEMENT AT SEKOLAH MENENGAH ATAS NEGERI 7 IN TANJUNGBALAI - Rahmayanti Panjaitan (UIN Sumatera Utara Medan, 2022)
This study aims to describe the implementation of the management of educational staff at the SMA Negeri 7 in Tanjung Balai. This study used qualitative research methods and collected data by using interviews, study documentation, and observation. The findings of this study found that the appointment of educational staff includes a selection of administrative requirements, and psychology through filling out forms and other requirements. The findings indicate that the implementation went well, and it can be seen from educational staff who cooperated, communicated with each other well, and were placed according to their knowledge. Supervision has been carried out properly, as well as the form of supervision carried out by the principal as the education manager. In addition, there are several supporting factors such as employees who are disciplined, creative, and responsible, have supporting infrastructure, coaching that is often followed by employees, and inhibiting factors faced regarding the rapid development of the times so that systems and technology tools are always developing in the implementation of administration.